Combined analysis of metagenome and transcriptome revealed the adaptive mechanism of different golden Camellia species in karst regions - Liu, Jianxiu; Jiang, Haidu; Huang, Yang; Zhong, Lisha; Xu, Qin; Yang, Quanguang; Liu, Shengyuan; Wei, Xiao; Liang, Yu; Chai, Shengfeng (Frontiers in Plant Science, 2023)
Camellia sect. Chrysantha is an important rare and protected plant species. Some golden Camellia species grow in karst soil while others grow in acidic soil. In order to study the adaptation mechanism of golden Camellia to the karst environment, four species of golden Camellia growing in the karst soil (Camellia pubipetala, Camellia perpetua, Camellia grandis, and Camellia limonia) and four species growing in the acidic soil (Camellia nitidissima, Camellia euphlebia, Camellia tunghinensis, and Camellia parvipetala) were selected for this study. Combining the metagenome and transcriptome, the structure and function of the rhizosphere microbial communities and the gene expression in roots of golden Camellia were analyzed. The results showed that the rhizosphere microbial communities in different golden Camellia were significantly different in abundance of Acidobacteria, Actinobacteria, Candidatus_Rokubacteria, Nitrospirae, Planctomycetes, and Candidatus_Tectomicrobia. The proportion of Candidatus_Rokubacteria was significantly higher in the rhizosphere soil of four species of golden Camellia grown in karst areas, compared to C. nitidissima, C. euphlebia, and C. tunghinensis. The linear discriminant analysis Effect Size showed that C. parvipetala was similar to karst species in the enrichment of ABC transporters and quorum sensing. During the transcriptome analysis, numerous upregulated genes in four karst species, including CYP81E, CHS, F3H, C12RT1, NAS, and CAD, were found to be enriched in the secondary metabolite synthesis pathway in the KEGG library, when compared to C. tunghinensis. This study provides information for plant adaptation mechanisms on the rhizosphere soil microbial composition and gene expression in secondary metabolic pathways to karst habitats and its distribution in karst areas.